The embodied palimpsest: dancing kinesthetic empathy in bharatanatyam - Zubko, Katherine C. (Body and religion, 2021)
In the South Asian dance style of bharatanatyam, the devotional bodies of dancers and the gods they portray model a performative porosity about "religious bodies." But what embodied resonances of religiosity transfer when the intention of the dancer or topic is not marked as devotional? Apsaras Arts' Agathi: The Plight of the Refugee (2017-18) offers an ethnographic case study through which I aim to deepen the theory around the porosity of bodies by developing the theoretical construct of an embodied palimpsest: a framework that allows previous "erased" layers to become present and interactive with later layers. I demonstrate how the choreographed gestures and rasas, or aesthetic moods, utilized to embody certain Hindu myths inform this danced portrayal of migrant experiences, but also note how the interactive layers of the palimpsest reshape classical theories about rasa, in particular karuna rasa, the mood of compassion, and can be used to particularize theories about kinesthetic empathy.